Thrombocytosis and central nervous system involvement in a case of canine acute megakaryoblastic leukemia. (19th July 2018) - Rochel, Daphné; Abadie, Jérôme; Robveille, Cynthia; Déqueant, Bérengère; Dagher, Elie; Roux, Françoise; Jaillardon, Laetitia
Abstract: This case report presents a 14‐month‐old female Poodle mix with acute megakaryoblastic leukemia based on a marked thrombocytosis, abnormal platelet morphology, circulating dwarf megakaryocytes, and blast cells in the blood. Bone marrow abnormalities included dysmegakaryopoiesis dygranulopoiesis, and an increased number of blast cells was observed in the blood. Extensive leukemic involvement was also found in the liver, spleen, lymph nodes, lungs, kidneys, and brain. The cytopathologic features of the abnormal circulating cells were highly suggestive of being megakaryocytic in origin, which was supported by negative myeloperoxidase staining and positive von Willebrand factor staining on immunocytochemistry (ICC). The neoplastic cells were also CD61 positive and had variable von Willebrand factor expression on ICC. Although there were only 25% blast cells in the bone marrow, which theoretically supported myelodysplastic syndrome, the hypothesis that this case represented acute myeloid leukemia of megakaryoblastic origin was confirmed by the continuous increase in circulating blast cell numbers during follow‐up visits and the extensive leukemic involvement of parenchymal organs.